Caries management by risk assessment. Issue 1 (25th January 2013) - Young, Douglas A.; Featherstone, John D. B.
Abstract Caries disease is multifactorial. Whether caries disease will be expressed and damage dental hard tissue is dependent on the patient's own unique make‐up of pathogenic risk factors and protective factors. Objectives This manuscript will review the science of managing caries disease based on assessing caries risk. Methods The caries balance/imbalance model and a practical caries risk assessment procedure for patients aged 6 years through adult will illustrate how treatment options can be based on caries risk. Results Neither the forms nor the clinical protocols are meant to imply there is currently only one correct way this can be achieved, rather are used in this manuscript as examples only. Conclusions It is important to have the forms and protocols simple and easy to understand when implementing caries management by risk assessment into clinical practice. The science of CAMBRA based on the caries balance/imbalance model was reviewed and an example protocol was presented.